Isolation, identification, and in silico characterisation of antimicrobial peptides from mangrove plants, Suaeda nigra and Suaeda maritima - Gathala, R P; Yamini, U; Gudivada, M (Plant Science Today, 2025)
Infectious diseases continue to be the primary cause of death, representing a significant public health issue globally. While antibiotics are an effective remedy, bacterial infections have developed resistance to these drugs, resulting in antibiotic treatment failure. Hence there is a quest for novel antibacterial agents from natural sources, including plants and other creatures. Plants possess the tendency to synthesise substances to defend themselves from challenging surroundings. This has prompted the investigation of antimicrobial peptides that are commonly derived and possess strong efficacy against pathogens. Moreover, the utilisation of mangroves in traditional medicine is garnering significant attention due to its reputation as an exceptional reservoir of bioactive substances for the treatment of cancer, diabetes, and others. Therefore, the current study concentrated on identifying the antimicrobial peptides from Suaeda nigra and Suaeda maritima. The analysis of leaf proteomes in S. nigra and S. maritima showed that the 15 and 20 KDa peptides exhibited strong antimicrobial activity, which were identified as Alpha-2-purothionin precursor and Vicin-like antimicrobial peptides-2-2-like proteins. The physicochemical characterization of Alpha-2-purothionin and Vicin-like antimicrobial peptides shows respective molecular weights of 14557.8 and 16353.78 Da. As well as their pI values were calculated as 5.13 and 6.11. The 3D structural analysis revealed that the Alpha-2-purothionin precursor and Vicin-like antimicrobial peptides showed an accurate model more similar to the templates PDB ID: 1nbl and PDB ID: 1fxzA. This study concluded that the identified proteins have significant antimicrobial potential against bacterial and fungal species, and their predicted structures were reliable.